2020
DOI: 10.1016/j.virusres.2020.198108
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin potentials against viral infections including COVID-19: Current evidence and new findings

Abstract: Highlights Viral infections are serious life-threatening and problematic human diseases. Melatonin can regulate human immune responses. Melatonin could be beneficial against different viral complications. In combination with other drugs, melatonin may play therapeutic role in COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 199 publications
1
98
0
Order By: Relevance
“…By contrast, exogenous estrogen application can increase OXT secretion, OTR mRNA expression in mouse brain [ 67 ], and intracardiac OTR signaling [ 68 ], which simulates the physiology of young women who are less susceptible than menopausal women to COVID-19. In addition, melatonin, a pineal hormone that has remarkable anti-inflammatory effects and can antagonize various viral infections including COVID-19 [ 69 ], can also regulate OXT release [ 70 ]. Thus, the susceptibility to COVID-19 is highly correlated with the activity of the OXT-secreting system.…”
Section: Oxt Functions Against Covid-19-associated CV Injuriesmentioning
confidence: 99%
“…By contrast, exogenous estrogen application can increase OXT secretion, OTR mRNA expression in mouse brain [ 67 ], and intracardiac OTR signaling [ 68 ], which simulates the physiology of young women who are less susceptible than menopausal women to COVID-19. In addition, melatonin, a pineal hormone that has remarkable anti-inflammatory effects and can antagonize various viral infections including COVID-19 [ 69 ], can also regulate OXT release [ 70 ]. Thus, the susceptibility to COVID-19 is highly correlated with the activity of the OXT-secreting system.…”
Section: Oxt Functions Against Covid-19-associated CV Injuriesmentioning
confidence: 99%
“…There appears to be no standard approach to treating cytokine release syndromes that currently addresses all three, and the vast majority address none, focusing instead on antagonizing cytokine functions. However, melatonin (N-acetyl-5-methoxy tryptamine) has recently emerged as an effective therapy for severe COVID-19 [ 246 , 247 , 248 , 249 , 250 , 251 ]. While melatonin is often thought of being mainly a sleep regulator, it also has widespread effects on the innate immunity—in particular, antagonizing TLR2, TLR4, TLR9, NLRP3 and, possibly, NOD2 [ 59 , 252 , 253 , 254 , 255 ].…”
Section: Discussionmentioning
confidence: 99%
“…The deadly outbreak of Covid-19 imposes immense therapeutic challenges. Interestingly, based on positive outcomes in many viral infections, melatonin therapy for viral infections like Covid-19 seems promising [ 198 , 199 ]. Clinically, it has been shown that melatonin has a therapeutic potential even in cases exhibiting obesity or diabetes in coexistence with Covid-19 [ 200 ].…”
Section: Therapeutic Role Of Melatonin On Post Infection Complicatmentioning
confidence: 99%